Medication adherence of cardiovascular patients after COVID-19: 6-month follow-up - A. R. Tyapaeva; E. A. Naumova; O. N. Semenova; Yu. V. Bulaeva; D. A. Tyapkina; A. A. Boroday (Российский кардиологический журнал, 2024)
Aim. To evaluate the relationship of various factors with adherence to therapy in cardiovascular patients after a coronavirus disease 2019 (COVID-19).Material and methods. The study included 284 patients (inpatients — 176, outpatients — 108) with cardiovascular diseases (hypertension, heart failure (HF), coronary artery disease, atrial fibrillation) after COVID-19. We collected data on cardiovascular history, made a questionnaire survey about COVID-19 course (symptoms, their severity, self-assessment of the disease severity). Paraclinical diagnostic investigations were carried out. In addition, 1, 3, 6 months after recovery, all respondents were invited for examination, laboratory tests, and survey using the Hospital Anxiety and Depression Scale (HADS). Cardiovascular therapy adherence was assessed at 1, 3 and 6 months after recovery and adherence to COVID-19 treatment 1 month after inclusion in the study by comparing the compliance of the drugs prescribed at discharge with its actual use.Results. In total, 212 respondents continued study participation after 1 month, while 64,2% were adherent to cardiovascular therapy and 56,6% — to COVID-19 therapy. Compliance at 3 and 6 months was 60,4% (n=212) and 52,8% (n=188), respectively. A moderate correlation was found between adherence to treatment and the persistence of apprehension 1 month after recovery (r=0,33, p<0,05), moderate or severe weakness during disease (r=0,31, p<0,05), COVID-19 severity (r=0,39, p<0,05). Inhospital respondents with lung tissue involvement >25% (n=64, 36,4%) were more adherent to standard cardiovascular therapy, prescribed in accordance with clinical guidelines (r=0,336, p<0,05). Adverse events in the form of a hypertensive crisis, arrhythmias, decompensated HF 1, 3, 6 months after recovery significantly increased the compliance with medical recommendations (p<0,05). Medication adherence regarding COVID-19 was associated with the disease severity, HF history, apprehension and anxiety, weakness, and decreased exercise tolerance (p<0,05).Conclusion. After 1 month, adherence to cardiovascular and COVID-19 therapy did not differ significantly (p>0,05). Compliance after 1, 3, 6 months was positively influenced by COVID-19 severity, the subjective feeling of weakness, apprehension and anxiety during disease and the persistence of a subjective feeling of anxiety after recovery. Adverse events (hypertensive crisis, arrhythmia, decompensated HF) during 1, 3 and 6 months after COVID-19 significantly (p<0,05) increased adherence to treatment.